THE RELATIONSHIP AMONG LEARNING STYLES, ECONOMIC STATUS, PARENTS’ EDUCATION BACKGROUND, AND ENGLISH PROFICIENCY IN UNIVERSITY STUDENTS - Nia Dayanti; Sofendi Sofendi; Eryansyah Eryansyah (University of Kuningan, 2021)
The objectives of this study were to find out (1) whether or not there were significant correlations between (1) learning styles (visual, audio, kinesthetic) and English proficiency, (2) economic status and English proficiency, (3) parents’ educational background and English proficiency, and (4) predictor variables (learning styles, economic status, and parents’ educational background) and the criterion variable (English proficiency). In this correlational study, the data collection was obtained through a Likert scale questionnaire and the documentation of TOEFL prediction results. 489 English Education Study Program students of Persatuan Guru Republik Indonesia (PGRI) University became the population of this study. The research sample was 114 students taken purposively using the purposive sampling technique. The study revealed that 46 students had visual learning styles, 38 others acquired a better understanding through audio-based learning activities, and 30 respondents preferred kinesthetic methods. Based on the result of the study, there was no correlation between English proficiency and visual learning style, audio learning style, and economic status. On the other hand, the study indicated a significant correlation between English proficiency with kinesthetic learning style and parents' educational background. Furthermore, there was also a significant correlation between the predictor variables (learning styles, economic status, and parents’ educational background) and the criterion variable (English proficiency).